The Decision to Quit Work in Bank Employees: A Phenomenological Study - Fatmawati, Indah; Sulastiana, Marina; Lestari Kadiyono, Anissa; Abidin, Zainal (Psikoborneo: Jurnal Ilmiah Psikologi, 2025)
The organization must cultivate job happiness for each employee to enhance the quality of its human resources. This research seeks to examine and evaluate job satisfaction as a determinant affecting the decision to resign among bank employees following a merger. The research employed qualitative methodologies through phenomenological study approaches. The research participants comprised three former bank employees aged 25 to 35, each with over three years of experience. The sampling strategy employed was purposeful, based on certain criteria, including experience in a merged bank and the decision to resign. Data collection was performed utilizing semi-structured in-depth interviews as the methodological instrument. The collected data were analyzed employing thematic analysis techniques to discern the principal themes associated with job satisfaction. The research findings reveal that key aspects influencing job satisfaction, including leadership, compensation, career advancement, and workload, have diminished following the merger. These circumstances compelled employees to choose resignation. This study concludes that job happiness significantly impacts employee decisions, particularly during organizational upheavals like mergers. This research suggests that organizations should prioritize employee job satisfaction to mitigate turnover and enhance human resource management successfully.